Boat noise affects meagre (Argyrosomus regius) hearing and vocal behaviour - Vieira, Manuel (2021)
Aquatic noise has increased in last decades imposing new constraints on aquatic animals' acoustic communication. Meagre (Argyrosomus regius) produce loud choruses during the breeding season, likely facilitating aggregations and mating, and are thus amenable to being impacted by anthropogenic noise. We assessed the impact of boat noise on this species acoustic communication by: evaluating possible masking effects of boat noise on hearing using Auditory Evoked Potentials (AEP) and inspecting changes in chorus sound levels from free ranging fish upon boat passages. Our results point to a significant masking effect of anthropogenic noise since we observed a reduction of ca. 20 dB on the ability to discriminate conspecific calls when exposed to boat noise. Furthermore, we verified a reduction in chorus energy during ferryboat passages, a behavioural effect that might ultimately impact spawning. This study is one of few addressing the effects of boat noise by combining different methodologies both in the lab and with free ranging animals.